2022
DOI: 10.3390/ijerph192416890
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Exploring the Theories Underlying the Improvement of Balance and Reduction in Falls Following Dual-Task Training among Older Adults

Abstract: Background: Balance impairment causes frequent falls in older adults, and preventing falls remains challenging. Dual-task (DT) training reduces falls by improving balance, but the precise theory is not fully understood. This review aims to explore the theories underlying the effectiveness of DT in improving balance and reducing falls in older adults. Methods: Eleven electronic databases were searched from database inception to June 2022. Two reviewers independently performed study screening and data extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…This improvement can be accounted to the contribution of the cerebellum in shifting an additionally demanding task such as dual-tasking to an automatic task with repeated practice (40,41). The attention theory helps understand this concept where repeated practice results in an improved capacity to shift attention to the secondary task during dual-tasking (42,43). We found some immediate effects of the intervention on the dynamic balance assessed using the SARAbal.…”
Section: Discussionmentioning
confidence: 70%
“…This improvement can be accounted to the contribution of the cerebellum in shifting an additionally demanding task such as dual-tasking to an automatic task with repeated practice (40,41). The attention theory helps understand this concept where repeated practice results in an improved capacity to shift attention to the secondary task during dual-tasking (42,43). We found some immediate effects of the intervention on the dynamic balance assessed using the SARAbal.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, despite the prevalence of gait disorders and falls among patients with CSVD (11,12,15), a definitive cure remains elusive. Previous studies have indicated that cognitive dual-task training is both safe and effective in improving various spatiotemporal gait parameters (52). Additionally, another systematic review confirmed that cognitive DTW training improves balance and reduces the incidence of falls in older adults (53).…”
Section: Performance DI Erences Between Cognitive and Motor Dtwmentioning
confidence: 85%
“…Such evidence provides a basis for the argument that task training, including both ST and DT training, can be used for promoting DT performance ( De Freitas et al, 2020 ; Chiaramonte et al, 2022 ). However, only few reviews discussed its effects in old participants ( Gallou-Guyot et al, 2020 ; Khan et al, 2022 ). Besides, it has been hypothesized that the combination of these two methods may provide greater efficacy and feasibility for DT improvement in the elderly.…”
Section: Introductionmentioning
confidence: 99%